White Matter Microstructural Integrity and Neurobehavioral Outcome of HIV-Exposed Uninfected Neonates. Issue 4 (January 2016) - Tran, Linh T.; Roos, Annerine; Fouche, Jean-Paul; Koen, Nastassja; Woods, Roger P.; Zar, Heather J.; Narr, Katherine L.; Stein, Dan J.; Donald, Kirsten A.
Abstract : Abstract: The successful implementation of prevention programs for mother-to-child human immunodeficiency virus (HIV) transmission has dramatically reduced the prevalence of infants infected with HIV while increasing that of HIV-exposed uninfected (HEU) children. Neuropsychological assessments indicate that HEU children may exhibit differences in neurodevelopment compared to unexposed children (HUU). Pathological mechanisms leading to such neurodevelopmental delays are not clear. In this observational birth cohort study we explored the integrity of regional white matter microstructure in HEU infants, shortly after birth. Microstructural changes in white matter associated with prenatal HIV exposure were evaluated in HEU infants (n = 15) and matched controls (n = 22) using diffusion tensor imaging and tract-based spatial statistics. Additionally, diffusion values were extracted and compared for white matter tracts of interest, and associations with clinical outcomes from the Dubowitz neonatal neurobehavioral tool were investigated. Higher fractional anisotropy in the middle cerebellar peduncles of HEU compared to HUU neonates was found after correction for age and gender. Scores on the Dubowitz abnormal neurological signs subscale were positively correlated with FA ( r = 0.58, P = 0.038) in the left uncinate fasciculus in HEU infants. This is the first study to present data suggesting that prenatal HIV exposure without infection is associated with altered white matter microstructural integrity in the neonatal period. Longitudinal studies of HEU infants as their brains mature are necessary to understand further the significance of prenatal HIV and antiretroviral treatment exposure on white matter integrity and neurodevelopmental outcomes.